Analisis Sensitivitas Parameter Rangkaian RLC Menggunakan Runge-Kutta Adaptif untuk Akurasi Numerik Optimal - Putra, David Eka; Fauzan, Reski Yulian; Salmeno, Amran Paso (Pustaka Galeri Mandiri, 2025)
This study investigates the numerical performance and parameter sensitivity of a RLC circuit solved using the adaptive Runge-Kutta-Fehlberg (RKF45) method. The mathematical model is formulated as a second-order ordinary differential equation and numerically integrated using RKF45 with local error control, then compared with the classical fourth-order Runge-Kutta (RK4) method using a fixed time step. Validation against the analytical steady-state solution shows that RKF45 achieves high accuracy with a lower Root Mean Square Error (RMSE ? 1.39×10??) while requiring 40% fewer integration steps than RK4. A sensitivity analysis based on normalized sensitivity coefficients is performed for ±10% variations of the R, L, and C parameters. The results reveal that inductance is the most dominant parameter influencing oscillatory dynamics, followed by capacitance, while resistance contributes mainly to damping. The sensitivity ranking is found to |. Overall, the findings display that RKF45 offers an efficient and accurate approach for RLC transient simulation and parameter sensitivity evaluation, making it suitable for applications that require high-precision dynamic analysis.